Reactive intermediate phase cold sintering in strontium titanate. Issue 36 (4th June 2018) - Boston, R.; Guo, J.; Funahashi, S.; Baker, A. L.; Reaney, I. M.; Randall, C. A.
Abstract : Strontium titanate ceramics (>96% theoretical) have been fabricated using a reactive intermediate phase cold sintering process with a range of starting-powder sizes. Abstract : Dense (>96% theoretical) strontium titanate ceramics were fabricated at 950 °C (conventional sintering temperature > 1400 °C) using a reactive intermediate phase cold sintering process. An aqueous solution of SrCl2 mixed with TiO2 nanoparticles was added to SrTiO3 powders and pressed at 180 °C to obtain a highly compacted green body. During the post-press heating step at 950 °C, the TiO2 and SrCl2 create in-filling micro-reactions around each grain resulting in dense (>96%) SrTiO3 ceramics. Nano- and micron-sized starting powders were used, demonstrating that this reactive intermediate phase cold sintering route can densify a wide range of starting powder sizes, as it not reliant on an amorphous-to-crystalline precipitation through the terrace ledge kink mechanism, as has been identified repeatedly in previous cold sintering mechanisms. Moreover, this process has the potential to densify a wide variety of functional oxides, as a range of different low-temperature chemical synthesis routes could be used.